Arjuna Tapa: A new creation dance - I Ketut Sariada; I Gede Oka Surya Negara; I Gede Mawan (Journal of Aesthetics, Creativity and Art Management, 2022)
: Arjuna Tapa New Creation Dance is a new creation inspired by Arjuna Tapa's story. It is about the sending of Arjuna by Yudhisthira to meditate to Mount Indrakila in the hope of obtaining a powerful weapon, which can be used in the face of a major war against the Kauravas. In the hermitage Arjuna received many temptations such as the temptation of a number of angels from heaven, the temptation of the big pig incarnate Momosimuka, and the temptation of the hunter Kirata. But all the temptations can be overcome properly and finally because of Arjuna's determination, Lord Shiva gave Pasupati's Arrow as a gift that would later be able to destroy his enemies. This dance is performed by seven male dancers, carrying arrows. These seven dancers in certain scenes will be divided into two characters, namely five male characters who play the five pandavas, namely Yudistira, Bima, Arjuna, Nakula, and Sahadewa. While the other two dancers play female characters as Dewi Kunti and Dewi Drupadi. The creation process went through the stages of exploration, experimentation, and formation. The structure of the work consists of four parts, namely pepeson, pengawak, pengecet, and pekaad. The dance moves refer to the line dance movements. This dance is accompanied by a gamelan gong that lasts 12 minutes. The message conveyed in Arjuna Tapa New Creative Dance is that a true warrior will succeed in doing his job well and smoothly if he can overcome all the obstacles and temptations he faces in achieving his goals.